1994
DOI: 10.1021/bi00197a040
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Mechanisms in the Catalysis of Human Immunodeficiency Virus Protease

Abstract: The most preferred residue in the substrates of human immunodeficiency virus (HIV-1) protease is glutamic acid in the P2' position. The catalytic importance of this charged residue has been studied to obtain a detailed insight into the mechanism of action, which will promote drug design to combat the virus. To this end, we have synthesized Lys-Ala-Arg-Val-Leu*Phe(NO2)-Glu-Ala-Nle (substrate E) and its counterpart containing the neutral Gln (substrate Q) in place of Glu. Kinetic analyses have shown that the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 24 publications
6
77
0
Order By: Relevance
“…2-Aminobenzoyl-Thr-Ile-Nle-Phe(NO 2 )-Gln-Arg (substrate QR) and 2-aminobenzoyl-Thr-Ile-Nle-Phe(NO 2 )-Glu-Arg (substrate ER) were prepared by solid phase synthesis (ABI 431A) and purified by high performance liquid chromatography. Lys-Ala-Arg-ValLeu-Phe(NO 2 )-Gln-Ala-Nle (substrate Q) and Lys-Ala-Arg-Val-LeuPhe(NO 2 )-Glu-Ala-Nle (substrate E) have already been described (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Aminobenzoyl-Thr-Ile-Nle-Phe(NO 2 )-Gln-Arg (substrate QR) and 2-aminobenzoyl-Thr-Ile-Nle-Phe(NO 2 )-Glu-Arg (substrate ER) were prepared by solid phase synthesis (ABI 431A) and purified by high performance liquid chromatography. Lys-Ala-Arg-ValLeu-Phe(NO 2 )-Gln-Ala-Nle (substrate Q) and Lys-Ala-Arg-Val-LeuPhe(NO 2 )-Glu-Ala-Nle (substrate E) have already been described (3).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (3), we have shown that a substrate of moderate specificity, Lys-Ala-Arg-Val-Leu-Phe(NO 2 )-Gln-AlaNle (substrate Q) is hydrolyzed at the Leu-Phe(NO 2 ) bond about 40 times faster by HIV-1 protease when Glu is substituted for the Gln in P2Ј. To establish the catalytic role of Glu in P2Ј, in this work the fluorogen 2-aminobenzoyl-Thr-Ile-NlePhe(NO 2 )-Gln-Arg (4) has been chosen which is one of the most effective substrates of HIV-1 protease.…”
mentioning
confidence: 88%
“…The cycle initiates with water activation by hydrogen-bonding interactions with the active site aspartate residues (1) (6, 7). Bell-shaped pH-rate profiles (8)(9)(10)(11)(12) have revealed an acidic pH optimum, and structural studies (13,14) suggest that the reactant-bound enzyme contains a single protonated Asp (with a di-Asp, net charge of −1) facilitating a general acid-base mechanism, which is common among many Asp proteases (7,15). Nucleophilic attack by the water generates a reversible gem-diol intermediate, (3) which has been observed structurally (16)(17)(18) and identified experimentally (19,20).…”
mentioning
confidence: 99%
“…However, we assumed that both retroviral proteases follow a similar catalytic reaction. Kinetic analysis has shown that HIV protease-catalyzed hydrolysis can have two different slow steps (Hyland et ai., 1991;Polgar et al, 1994). One of the slow steps was proposed to be the binding of Table 2 are shown.…”
Section: Interaction Energymentioning
confidence: 99%
“…Reaction coordinates consistent with experimental data for HIV protease catalysis from enzyme (E) and substrate ( S ) via intermediate (I) to enzyme and products (P) are shown. Two possible slow steps (Hyland et al, 1991;Polgar et al, 1994) Discussion of the entropic contribution…”
Section: E + P E + S 4 -W E Smentioning
confidence: 99%